Mekanisme Peningkatan Efisiensi Operasional melalui Digitalisasi Manajemen SHE: Peran Mediasi Kinerja Keselamatan di Proyek Batu Hijau - Wira Sanjaya Tapitapi; Tomy Dwi Cahyono (LPPM Institut Pendidikan Nusantara Global, 2026)
This study develops an integrated model explaining how digitalization of Safety, Health, and Environment (SHE) management can improve safety performance and operational efficiency in heavy-equipment service activities at the Batu Hijau Project. The model combines a socio-technical systems perspective, digital transformation capability, and the safety-performance framework. A quantitative explanatory case design was specified and evaluated with Partial Least Squares Structural Equation Modeling (PLS-SEM). Because project-level primary data were not supplied for this manuscript-development stage, the analytical model was tested using a calibrated simulated dataset of 132 observations representing frontline, supervisory, technical, and SHE-related roles. The measurement model met reliability and convergent-discriminant validity criteria. Digital SHE management showed a positive effect on safety performance (β = 0.718; p < 0.001) and operational efficiency (β = 0.415; p < 0.001), while safety performance positively affected operational efficiency (β = 0.459; p < 0.001). The indirect effect was also significant (β = 0.329; p < 0.001), indicating partial mediation. The findings suggest that integrated digital workflows, mobile reporting, real-time dashboards, traceable corrective actions, and data-driven learning can simultaneously strengthen preventive safety control and reduce administrative and coordination losses. The paper offers a practical digital-SHE architecture and measurable implementation priorities for mining-service operations.